Supercapattery performance of carbon nanofibers decorated with poly(3,4-ethlenedioxythiophene) and cobalt oxide - Azman, Nur Hawa Nabilah (Elsevier, 2022)
Supercapattery epitomizes the next level of energy storage technology which demonstrates the pros of a supercapacitor and a battery. In this work, we developed a positive electrode of supercapattery comprised of porous functionalized carbon nanofibers (pfCNFs) as a template for the electrodeposition of poly(3,4-ethylenedioxythiophene) (PEDOT) and incorporation of cobalt oxide (Co3O4) through hydrothermal and annealing. Interestingly, the composite displays a flower-like structure observed on the fibers. The functionalized carbon nanofibers/poly(3,4-ethylenedioxythiophene)/cobalt oxide (pfCNFs/PEDOT/Co3O4) exhibited obvious redox peaks demonstrating its battery type property with high specific capacity (Csp) and specific capacity (Cs) of 849.65 F g-1 and 679.72 C g-1, respectively. As for the real application, the positive electrode of pfCNFs/PEDOT/Co3O4 and nitrogen-doped graphene as a negative electrode was assembled with a polyvinyl alcohol/potassium hydroxide gel used as a separator. The pfCNFs/PEDOT/Co3O4//NDG displayed specific energy of 14.54 Wh kg-1 and specific power of 1726.96 W kg-1 at 2 A g-1. In addition, the device also exhibited remarkable cycling stability with 106.26% capacitance retention over 2000 cycles revealing its prospect as an electrode for supercapattery.